RENEWAL OF CRIMINAL LAW AGAINST ABUSE OF CREDIT CARDS - Nugraha, Eka; Akub, Sykri; Rifai, Badriyah; Arie, Martehen (Journal of Humanity, 2015)
The use of credit cards for payment in lieu of cash since the introduction of the first credit card ever more widely known and used by people. On the early introduction of this credit card, the wearer is limited to certain circles. However, a few decades later the credit card industry primarily enter the end of the Decade of the 1970s, has penetrated almost throughout all parts of the world, including Indonesia. A credit card is issued by most commonly used by the public and apply the current International consists of a range of brands, among others, a very popular one is Visa and Master Card are each issued by the credit card company international and Master Card International.In practice many found the works in banking that may be subject to sanctions as set forth in the book of the law of criminal law (Criminal Code).